Identification and Characterization of a Novel 38.5-Kilodalton Cell Surface Protein of Staphylococcus aureus with Extended-Spectrum Binding Activity for Extracellular Matrix and Plasma Proteins - Hussain, Muzaffar (American Society for Microbiology, 2001)
The ability to attach to host ligands is a well-established pathogenic factor in invasive Staphylococcus aureus disease. In addition to the family of adhesive proteins bound to the cell wall via the sortase A (srtA) mechanism, secreted proteins such as the fibrinogen-binding protein Efb, the extracellular adhesion protein Eap, or coagulase have been found to interact with various extracellular host molecules. Here we describe a novel protein, the extracellular matrix protein-binding protein (Emp) initially identified in Western ligand blots as a 40-kDa protein due to its broad-spectrum recognition of fibronectin, fibrinogen, collagen, and vitronectin. Emp is expressed in the stationary growth phase and is closely associated with the cell surface and yet is extractable by sodium dodecyl sulfate. The conferring gene emp (1,023 nucleotides) encodes a signal peptide of 26 amino acids and a mature protein of a calculated molecular mass of 35.5 kDa. Using PCR, emp was demonstrated in all 240 S. aureus isolates of a defined clinical strain collection as well as in 6 S. aureus laboratory strains, whereas it is lacking in all 10 S. epidermidis strains tested. Construction of an allelic replacement mutant (mEmp50) revealed the absence of Emp in mEmp50, a significantly decreased adhesion of mEmp50 to immobilized fibronectin and fibrinogen, and restoration of these characteristics upon complementation of mEmp50. Emp expression was also demonstrable upon heterologous complementation of S. carnosus. rEmp expressed in Escherichia coli interacted with fibronectin, fibrinogen, and vitronectin in surface plasmon resonance experiments at a K(d) of 21 nM, 91 nM, and 122 pM, respectively. In conclusion, the biologic characterization of Emp suggests that it is a member of the group of secreted S. aureus molecules that interact with an extended spectrum of host ligands and thereby contribute to S. aureus pathogenicity.